The Influence of Extensive Reading on EFL G12 students’ Vocabulary Acquisition and the main facilitating factors - Moussa, Ahmad (2013)
The current study investigates the real influence of extensive reading as an approach of reading on foreign language vocabulary acquisition; it explores whether extensive reading materials can enhance EFL students' lexical knowledge. It also discusses the main factors which facilitate and support the incidental acquisition of vocabulary through extensive reading newspaper articles, and focuses on the role of words reoccurrences as a leading factor that helps EFL students acquire and understand unfamiliar vocabulary. This study investigates 45 grade 12 Arab students in a private school in the UAE context. It adopts a mixed methods approach of quantitative and qualitative instruments to obtain the necessary data. A questionnaire, some semi-structured interviews and Pre- and post tests are conducted on a number of students after they are divided into three groups; each group is given different treatment of extensive reading articles. The results are analysed through the SPSS to answer the research questions of the significant effect of extensive reading on EFL vocabulary acquisition. The findings of the research reveal the real influence of Extensive reading articles on the readers' vocabulary acquisition. The results vary from one group to another according to the type of treatment they are given. Group C students, who are given nine reading articles, outperform their colleagues in both groups, A and B who read three or six articles respectively, which means the items occurring more frequently in the text are more likely to be learned. The findings also reveal that some words are more likely to be incidentally acquired than others; in terms of contextual use, word types and parts of speech. Therefore, the research confirms the role of extensive reading materials in facilitating the process of vocabulary incidental acquisition and learning, and opens more possibilities for future investigations toward this topic.